Theoretical analysis and experimental study on physical explosion of stratospheric airship envelope - Song, Lin; Yang, Yanchu; Zheng, Zhidong; He, Zeqing; Zhang, Xiaojun; Gao, Heng; Guo, Xiqing (Frontiers in Materials, 2023)
The shock wave released from physical explosion of a pressurized stratospheric airship can produce serious damage to the environment. Shock wave overpressure can measure the degree of damage that an explosion can cause to such things as buildings and the human body. To obtain the overpressure from an airship envelope explosion, explosion energy must first be conducted. Explosion energy is derived based on Brode’s equation, Brown’s equation, and Crowl’s equation. An equivalent TNT computational model is then applied to calculate the overpressure of the explosion energy. In order to verify the accuracy of the computational model, a ground test must be conducted. The experimental result shows that a computational model based on Crowl’s equation is more accurate than the other two. Finally, the effect of geometric scale ratio, pressure difference, and the gas of the explosion overpressure is discussed. This paper can provide a relatively effective calculation method for shock wave overpressure for an airship envelope explosion.